High-Dose Steroids in Rasmussen's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Ten of 17 patients with Rasmussen's syndrome receiving IV methylprednisolone and/or oral predisolone, and eight of nine patients receiving immunoglobulins showed some short-term reduction in seizure frequency in a multicenter international report.